ANALISIS PENERAPAN HYBRID CONTRACT PADA PRODUK UNIT LINK DI ASURANSI JIWA PT PRUDENTIAL PAMEKASAN - Subairi Subairi (LP2M IAI Miftahul Ulum Pamekasan, 2020)
The study of insurance in Islamic law is a new thing, and has never been found in classical fiqh literature. The discussion of insurance in the area of ​​Islamic sciences only appeared at the stage of the birth of contemporary scholars. Included in relation to the application of hybrid contracts in insurance. Along with the development of life insurance products, insurance companies not only provide traditional insurance services that are purely protection, but also provide various supporting services for financial planning in the future, according to their needs and financial capabilities, whether they are personal, family or group. one service offered is a combination of insurance and investment, known as Unit Link. The application of a hybrid contract on the unit link in Prudential Pamekasan life insurance is a contract between a participant and a sharia insurance company using a tijarah contract called wakalah bil ujrah, and an easyarabah / musyarakah contract on its investment. and covenants among participants using the tabarru contract 'in the form of a grant, and Qard. The advantages and disadvantages of implementing Unit Link hybrid contracts at PT Prudential Pamekasan syariah and conventional can be seen from the reasons customers choose insurance and the most influential is the rate of premium returns and the investment returns, in this case PRUsyariah is relatively smaller than conventional. 3). The implementation of the Prudential PRUlink Pamekasan hybrid contrac Unit Link in the perspective of Islamic economics can produce multiple legal interpretations between those who allow and those who do not.